Feedback about more accurate versus less accurate trials: differential effects on self-confidence and activation - Badami, R.; Vaezmousavi, M.; Wulf, G.; Namazizadeh, M. (Research Quarterly for Exercise and Sport, 2012)
One purpose of the present study was to examine whether self-confidence or anxiety would be differentially affected by feedback from more accurate rather than less accurate trials. The second purpose was to determine whether arousal variations (activation) would predict performance. On Day 1, participants performed a golf putting task under one of two conditions: one group received feedback on the most accurate trials, whereas another group received feedback on the least accurate trials. On Day 2, participants completed an anxiety questionnaire and performed a retention test. Skin conductance level, as a measure of arousal, was determined. The results indicated that feedback about more accurate trials resulted in more effective learning as well as increased self-confidence. Also, activation was a predictor of performance.